2006
DOI: 10.1029/2005ja011449
|View full text |Cite
|
Sign up to set email alerts
|

A new shock fitting procedure for the MHD Rankine‐Hugoniot relations for the case of small He2+ slippage

Abstract: [1] To study MHD shocks in space, it is important to find the shock frame of reference from the observed plasma and magnetic field parameters. These shock parameters have to satisfy the Rankine-Hugoniot relations. In this study we present a novel procedure for shock fitting of the one-fluid anisotropic Rankine-Hugoniot relations and of the time difference between two spacecraft observations in the case of small He 2+ slippage. Here, a Monte-Carlo calculation and a minimization technique are used. The observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(72 citation statements)
references
References 34 publications
1
71
0
Order By: Relevance
“…Then a minimization technique is used; with this, a best fit solution that satisfies the R-H relations and that is closest to the data mean is obtained. More detailed descriptions about the procedure were given by Lin et al (2006).…”
Section: Methods Of Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Then a minimization technique is used; with this, a best fit solution that satisfies the R-H relations and that is closest to the data mean is obtained. More detailed descriptions about the procedure were given by Lin et al (2006).…”
Section: Methods Of Analysismentioning
confidence: 99%
“…In searching for a shock frame, several methods have been developed to determine the shock normal vector n s , such as the coplanarity method mentioned above, the minimum variance analysis method, and the triangulation method (Knetter et al 2004). Here, we apply a shock fitting procedure based on the Monte Carlo calculation proposed by Lin et al (2006). Lin et al (2006) use the upstream and downstream observed mean variables and associated errors to randomly generate arrays of the variables needed for the fitting procedure, and every generated array for these variables satisfy the R-H relations.…”
Section: Methods Of Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the ion-electron temperature ratio, the pressure anisotropy, and the gradient of the heat flux are all free parameters in the MHD R-H jump conditions. It has been shown that both the pressure anisotropy and the gradient of the heat flux can modify the R-H jump conditions of the shock waves [e.g., Chao, 1970;Chao and Goldstein, 1972;Lyu and Kan, 1986;Lin et al, 2006] and the rotational discontinuities [Hudson, 1971]. It should also be true for the CDs.…”
Section: Introductionmentioning
confidence: 99%